Venture Clienting in Corporate Practice: What type of Established Companies are Using the Venture Client Model? - Haarmann, Lennard; Jobelius, Johannes J.; Machon, Fabian; Rabe, Martin; Kühn, Arno; Dumitrescu, Roman (European Conference on Innovation and Entrepreneurship)
Start-ups have become a pillar of EC' open innovation initiatives. With the aim of accessing start-up innovation, established companies (EC) use various corporate venturing modes. However, as established corporate venturing modes (e.g. corporate venture capital or accelerators) do not provide direct access to start-up innovation, the venture client model (VCLM) is receiving increasing attention in corporate practice. In the VCLM, ECs become paying customers of start-ups without taking equity - they become venture clients. In joint pilot projects, they apply start-up solutions to their products, processes or business models in order to solve relevant business problems and create strategic impact for increased competitiveness. The literature lists different EC using the VCLM such as BMW, Bosch, Continental, Daimler, Siemens, or ZF. This suggests that the VCLM is only used in EC with tens of thousands of employees, from Germany and in technology-intensive sectors such as automotive, mechanical engineering or telecommunications. On the other hand, GIMMY describes the suitability of the VCLM for any EC. However, in order to develop practical solutions to the challenges of the VCLM (e.g. slow purchasing, legal and IT processes or lack of acceptance of start-ups as collaboration partners), it is necessary to know the users (type of EC) of these solutions. Therefore, the aim of this paper is to characterize the EC using the VCLM with respect to industry, size and regionality.

Engineering Genetics - Towards the Double Helix Model for Integrative Product and Production Design - Disselkamp, Jan-Philipp; Seidenberg, Tobias; Lick, Jonas; Ptock, Lukas; Hovemann, Aschot; Dumitrescu, Roman (Proceedings of NordDesign 2024)

Model-Based Handling of Variability in Offer Management in Mechanical and Plant Engineering - Wilke, Daria; Bremer, Christian; Disselkamp, Jan-Philipp; Dumitrescu, Roman (Proceedings of NordDesign 2024)

Guiding The Transformation To A Digital Factory Twin: Towards An Enterprise-Architecture-Management-based Approach With The Help Of A Capability Map - Lick, Jonas; Weller, Julian; Brock, Jonathan; Pathak, Shantanu; Disselkamp, Jan-Philipp; Kühn, Arno; Dumitrescu, Roman (Procedia CIRP)

Spearhead Data-Driven Model-Based Systems Engineering: Interview Study on Definition, Preconditions, Challenges, Potentials, and Use Cases - Tissen, Denis; Wiederkehr, Ingrid; Bernijazov, Ruslan; Koldewey, Christian; Dumitrescu, Roman (Proceedings of NordDesign 2024)

A Maturity Model for Data-Driven Model-Based Systems Engineering for Producing Companies - Tissen, Denis; Bernijazov, Ruslan; Koldewey, Christian; Dumitrescu, Roman (Proceedings of the 26th International DSM Conference (DSM 2024), Stuttgart, Germany)

Towards Automated Design: Automatically Generating Modeling Elements with Prompt Engineering and Generative Artificial Intelligence - Kulkarni, Pranav Jayant; Tissen, Denis; Bernijazov, Ruslan; Dumitrescu, Roman (Proceedings of NordDesign 2024)

The Venture Client Model and Its Challenges for Established Companies - Haarmann, Lennard; Machon, Fabian; Rabe, Martin; Asmar, Laban; Kuhn, Arno; Dumitrescu, Roman (Proceedings of NordDesign 2024)

Data from start to finish: A System Life Cycle Data Map - Tissen, Denis; Wiederkehr, Ingrid; Koldewey, Christian; Dumitrescu, Roman (Procedia CIRP)

Toward Intelligent Generation of System Architectures - Von Heissen, Oliver; Hanke, Fabian; Mpidi Bita, Isaac; Hovemann, Aschot; Dumitrescu, Roman (Proceedings of NordDesign 2024)

Reference Architecture for the Integration of Prescriptive Analytics Use Cases in Smart Factories - Weller, Julian; Migenda, Nico; Naik, Yash; Heuwinkel, Tim; Kühn, Arno; Kohlhase, Martin; Schenck, Wolfram; Dumitrescu, Roman (Mathematics)
Prescriptive analytics plays an important role in decision making in smart factories by utilizing the available data to gain actionable insights. The planning, integration and development of such use cases still poses manifold challenges. Use cases are still being implemented as standalone versions; the existing IT-infrastructure is not fit for integrative bidirectional decision communication, and implementations only reach low technical readiness levels. We propose a reference architecture for the integration of prescriptive analytics use cases in smart factories. The method for the empirically grounded development of reference architectures by Galster and Avgeriou serves as a blueprint. Through the development and validation of a specific IoT-Factory use case, we demonstrate the efficacy of the proposed reference architecture. We expand the given reference architecture for one use case to the integration of a smart factory and its application to multiple use cases. Moreover, we identify the interdependency among multiple use cases within dynamic environments. Our prescriptive reference architecture provides a structured way to improve operational efficiency and optimize resource allocation.

On the Current State of Industrial Data Science: Challenges, Best Practices, and Future Directions - von Enzberg, Sebastian; Weller, Julian; Brock, Jonathan; Merkelbach, Silke; Panzner, Melina; Lick, Jonas; Kühn, Arno; Dumitrescu, Roman (Procedia CIRP)

Design decisions for integrating Prescriptive Analytics Use Cases into Smart Factories - Weller, Julian; Migenda, Nico; Enzberg, Sebastian von; Kohlhase, Martin; Schenck, Wolfram; Dumitrescu, Roman (Procedia CIRP)

Applying Artificial Intelligence in the Smart Factory: Lessons Learned from real-world use cases - Hartmann, Stefan; Brock, Jonathan; Kühn, Arno; Dumitrescu, Roman (Procedia CIRP)

Prescriptive Analytics Data Canvas: Strategic Planning For Prescriptive Analytics In Smart Factories - Weller, Julian; Migenda, Nico; Kühn, Arno; Dumitrescu, Roman

Using Multi-Modal LLMs to Create Models for Fault Diagnosis - Merkelbach , Silke; Diedrich , Alexander; Sztyber-Betley, Anna; Travé-Massuyès, Louise; Chanthery , Elodie; Niggemann , Oliver; Dumitrescu , Roman (Open Access Series in Informatics (OASIcs))

Technical Readiness of Prescriptive Analytics Platforms: A Survey - Niederhaus, Marvin; Migenda, Nico; Weller, Julian; Schenck, Wolfram; Kohlhase, Martin (2024 35th Conference of Open Innovations Association (FRUCT))

Challenges and Research Needs in the Offer Phase of Special Purpose Machinery and Plant Engineering – A Qualitative Study with Industry Experts - Wilke, Daria; Mansheim, Johanna; Dumitrescu, Roman (IEEE Engineering Management Review)

PID-Gen: Towards an Algorithm for the Generation of Random P&IDs - Merkelbach, Silke; Heuwinkel, Tim; Dumitrescu, Roman (2024 IEEE 29th International Conference on Emerging Technologies and Factory Automation (ETFA))

Investigation of validation methods for system design in the B2B sector - Humpert, Lynn; Wilke, Daria; Tissen, Denis; Rummney, Johannes; Anacker, Harald; Dumitrescu, Roman (2024 IEEE International Systems Conference (SysCon))